2017
DOI: 10.1159/000480666
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the Number of Metastatic Tumors Treated by Stereotactic Radiosurgery on the Dose to Normal Brain: Implications for Brain Protection

Abstract: Purpose/Objectives: The purpose of this study was to evaluate the effect of the number of brain lesions for which stereotactic radiosurgery (SRS) was performed on the dose volume relationships in normal brain. Materials and Methods: Brain tissue was segmented using the patient's pre-SRS MRI. For each plan, the following data points were recorded: total brain volume, number of lesions treated, volume of brain receiving 8 Gy (V8), V10, V12, and V15. Results: A total of 225 Gamma Knife® treatments were included i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 14 publications
1
8
0
Order By: Relevance
“…One recent analysis suggests acceptable safety and efficacy profiles associated with administration of SRS to ≤15 metastases 19 . Another retrospective study estimated the radiation dose delivered to normal brain as a function of the total tumor volume treated with SRS 20 . To complement these emerging data, we used a novel approach to estimate that treating 12–13 tumors per day over 10 days would deliver the dose of radiation to healthy brain tissue typically associated with a standard course of WBRT (3 Gy x 10 fractions).…”
Section: Discussionmentioning
confidence: 99%
“…One recent analysis suggests acceptable safety and efficacy profiles associated with administration of SRS to ≤15 metastases 19 . Another retrospective study estimated the radiation dose delivered to normal brain as a function of the total tumor volume treated with SRS 20 . To complement these emerging data, we used a novel approach to estimate that treating 12–13 tumors per day over 10 days would deliver the dose of radiation to healthy brain tissue typically associated with a standard course of WBRT (3 Gy x 10 fractions).…”
Section: Discussionmentioning
confidence: 99%
“…Studies by Xue et al, (2015) and Rivers et al, (2017) in Gamma Knife treatment found that the total PTV volume was the influencing factor of the normal brain mean dose, and the number of targets did not influence the same. We observed in Linac-based SIMT planning that the normal brain dose tends to increase with the number of targets.…”
Section: Discussionmentioning
confidence: 92%
“… 60 The threshold of >3 J was not dependent on the number of lesions treated, but was met when total tumor volume exceeded 25 cc. 61 Importantly, cognitive outcomes have not been rigorously evaluated in patients receiving SRS for >10 metastases, although this is being actively examined in multiple open phase III trials. 52 …”
Section: Management Of >10 Metastasesmentioning
confidence: 99%